2013
DOI: 10.1055/s-0033-1348881
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Short-Term Low-Intensity Exercise Training on Association of Oxygen Free Radicals and Nitric Oxide Production in Patients with Acute Myocardial Infarction

Abstract: Oxygen, although is highly required for living, can be toxic because it can be easily changed into oxygen free radicals (reactive oxygen species, ROS) and generates oxidative stress. [1][2][3][4][5] This oxidative stress will cause endothelial lesion and will be responded by endothelial cells through nitric oxide (NO) response and immunological response pathway. 6-8 The immunological response begins by increasing cytokines production, activated coagulation factors, and reactivation of platelet in acute thrombo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Similarly, current findings showed an inverse association between vitamin D and NOx. While NOx has shown positive associations between high systolic blood pressure and triglycerides in the girls group, no associations were found with total cholesterol, HDL, and vitamin D. Inverse association has been shown in NOx and systolic blood pressure among patients with myocardial infraction [ 34 ]. In pregnant women with hypertension, NOx synthesis was significantly reduced with increased levels of triglycerides and cholesterol [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, current findings showed an inverse association between vitamin D and NOx. While NOx has shown positive associations between high systolic blood pressure and triglycerides in the girls group, no associations were found with total cholesterol, HDL, and vitamin D. Inverse association has been shown in NOx and systolic blood pressure among patients with myocardial infraction [ 34 ]. In pregnant women with hypertension, NOx synthesis was significantly reduced with increased levels of triglycerides and cholesterol [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Baraas et al, (2013) showed that there was no positive correlation between F 2 -Isoprostane and Nitric Oxide (NO). Nitric Oxide (NO) is a negative predictor variable for F 2 -Isoprostane levels because the higher the Nitric Oxide (NO) level, the lower the F 2 -Isoprostane.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress will create lesions on the endothelium with the Nitric Oxide (NO) reaction. If there is a decrease in Nitric Oxide (NO) levels in the vascular endothelium, then the body's adaptive capacity decreases and pathological changes occur in metabolism and can potentially lead to coronary heart disease and vascular damage (Astutik et al, 2014;Baraas et al, 2013;Persio et al, 2020). The purpose of this study was to determine the formation of free radicals through F 2 -Isoprostane levels and the function of the endothelium and blood vessels through Nitric Oxide (NO) levels when cycling 30 Km.…”
Section: Introductionmentioning
confidence: 99%